Behavior of Transverse Fillet Welds: Parametric and Reliability Analyses - Ng, Anthony K.F.; Driver, Robert G.; Grondin, Gilbert Y. (Engineering Journal, 2004)
Transverse fillet weld specimens were tested to assess the influence of various parameters on fillet weld strength and ductility and to evaluate the level of safety being provided currently by North American design standards. Details of the test procedures and results are reported in the companion paper by Ng, Deng, Grondin, and Driver, also published in the 2nd Quarter 2004 issue of the Engineering Journal. The variables included in the study were the filler metal classification (including classifications both with and without a toughness requirement), fillet weld size and number of passes, electrode manufacturer, steel fabricator, root notch orientation, and test temperature.